Effect of Combination of Slow Deep Breathing and Ice Therapy towards Comfort Level in Arteriovenous Fistula Insertion of Hemodialysis Patients in PKU Muhammadiyah Hospital Yogyakarta - Nur Isnaini; Titiek Hidayati; Sri Sumaryani (Indonesian Journal of Clinical Pharmacy, 2018)
Patients with chronic renal disease undergoing hemodialysis will have arteriovenous (AV) fistula insertion for 2–3 times a week or an average of ten punctures per month. Intervention of comfort technical with combination of slow deep breathing and ice therapy help to reduce discomfort due to AV fistula insertion. The objective of this research was to determine the effect of combination of slow deep breathing and ice therapy on comfort level of AV fistula insertion. This research was conducted from January until February 2015 at PKU Muhammadiyah Hospital Yogyakarta. Type of this research is a quasi experiment with only post test group design with control group. The sample was divided into 20 patients in intervention group and 20 patients in control groups through simple random sampling technique. For each group, discomfort level was measured using Visual Analog Scale after AV fistula insertion. In intervention group, respondents were given a combination of deep breathing and ice therapy on acupuncture points LI4 10 minutes before insertion. The data were collected twice and analyzed of the difference between intervention group and control group using Chi-Square, Wilcoxon and Mann-Whitney test. There was a significant difference between intervention group and control group using Visual Analog Scale discomfort with p=0.000. Provision of comfort technical intervention with combination of slow deep breathing and ice therapy proved to improve the comfort of hemodialysis patients while undergoing insertion of AV fistula.Keywords: AV fistula insertion, combination of slow deep breathing and ice therapy, comfort level Pengaruh Kombinasi Nafas Dalam dan Terapi Es terhadap Level Kenyamanan Insersi Fistula Arteri-vena Pasien Hemodialisis di Rumah Sakit PKU Muhammadiyah YogyakartaPasien penyakit ginjal kronik yang menjalani hemodialisis akan mengalami insersi fistula arteri-vena (AV fistula) selama 2–3 kali seminggu atau rata-rata akan mengalami sepuluh tusukan setiap bulan. Intervensi comfort technical dengan kombinasi nafas dalam dan terapi es membantu mengurangi ketidaknyamanan akibat insersi AV fistula. Penelitian ini bertujuan untuk mengetahui pengaruh kombinasi nafas dalam dan terapi es terhadap level kenyamanan insersi AV-Fistula. Penelitian dilakukan di Rumah Sakit PKU Muhammadiyah Yogyakarta pada bulan Januari sampai Februari 2015. Jenis penelitian ini yaitu quasi eksperimental dengan only post test group design with control group. Sampel dibagi menjadi 20 pasien kelompok intervensi dan 20 pasien kelompok kontrol melalui teknik simple random sampling. Masing-masing kelompok dilakukan pengukuran ketidaknyamanan menggunakan Visual Analog Scale setelah insersi AV fistula. Pada kelompok intervensi, diberikan kombinasi nafas dalam dan terapi es pada titik akupunktur LI4 10 menit sebelum insersi. Pengambilan data dilakukan dua kali dan dianalisis perbedaan antara kelompok intervensi dan kontrol menggunakan uji Chi-Square, Wilcoxon dan Mann-Whitney. Terdapat perbedaan yang signifikan antara kelompok intervensi dan kelompok kontrol dengan menggunakan skala ketidaknyamanan Visual Analog Scale dengan nilai p=0,000. Pemberian intervensi comfort technical dengan kombinasi nafas dalam dan terapi es terbukti dapat meningkatkan kenyamanan pasien hemodialisis saat menjalani insersi AV-Fistula.Kata kunci: Insersi AV fistula, kombinasi nafas dalam dan terapi es, level kenyamanan